The Communication Performance Analysis of the In Room Dining Division at Hotel “A” as the Basis for the Formation of Organizational Culture - Tham, Michael; Winarko, Hilarius Bambang (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Communication performance and organizational culture are closely related, in the process an individual's communication performance reflects their organization's culture. Every company has its organizational culture, including Hotel “A," which is one of the 5-star international hotels in Jakarta, also experiencing issues with its organizational culture. This study employs descriptive research with a qualitative approach. The method used in this research is interview with employees from the in-room dining division at Hotel “A”, that is a 2 active members of the organization. The research findings reveal problems in the communication performance at Hotel “A”. For instance, in terms of ritual performance, there is a company culture of working overtime. Additionally, in terms of passion performance, the abundance of job tasks in the in-room dining division diminishes the manager's focus, especially for unexperienced leader in a similar divisions. Social performance shows the existence of factions within the organization but with no significant impact on operations. Political performance manifests as a sense of superiority over certain groups (seniority). Lastly, enculturation performance indicates differences in training between staff levels and daily workers, creating clearer disparities. All of these issues stem from the inadequate communication performance in the in-room dining division at Hotel “A”. If left unaddressed, they may lead to demotivation, a decline in work ethic, and feelings of saturation among employees, ultimately impacting the formation of the company's culture. The researcher suggests that management and Human Resources collaborate to address these issues, fostering open communication and welcoming input to establish positive organizational culture.